Redesign of Wallet Production Facility Layout Using ARC and Simulation at Fanri Collection - Miranda, Suci; Helia, Vembri Noor; Aldefka A. Anafachsyah, Audrie; Sahirah Elfahmi, Azzati; Raihan; Arum Sari, Sekar (UPT Publikasi Ilmiah UNISBA, 2024)
Abstract. The development of technology at this time causes competition in the accessories and fashion industry. This situation has caused an increase in the number of requests for products at Fanri Collection, a producer of leather craft accessories. To survive and win the competition, companies need to increase productivity. One way of resolving the issue is by designing the layout and production facilities to minimize the distance of material handling in the production process. This research aims to design layout and production facilities on wallet products with the Discrete Event Simulation (DES) method using FlexSim 21.0 software and Activity Relationship Chart (ARC) to analyze the amount of output and get a proposed facility layout. Based on the simulation results, in producing 200 units of wallets, the initial total material handling distance is 20.667 meters with a cycle time of 1 day, 5 hours, and 3 minutes. After making improvements with ARC, the total material handling distance is reduced to 17.475 meters with a cycle time of 1 day, 4 hours, and 48 minutes. Thus, the improvement can minimize material handling distance by 3.192 meters and reduce cycle time by about 15 minutes.